The Nurse Lecturer’s Competencies: A Systematic Review - Novita, Dian; Sri Hariyati, Roro Tutik; Masfuri, Masfuri; Besral, Besral (Universitas Aisyah Pringsewu, 2024)
The development of nursing education has undergone acceleration in various aspects. The effect of rapid digitalization, the requirements to become professional nurses, increasingly stringent regulations, global open competition and a variety of diseases that are increasingly developing in society have all added to the need for nurse lecturers who have relevant competencies in educating future nurse candidates. Clinical education for nurses is an integrated part of the nursing curriculum and a fundamental for bridging the gap between practice and theory. Based on the needs of students to oversee the process of assessing the competence of nurse lecturers both in academics and in practice in the field aims to maintain quality and improve competence. The aim of this systematic review is to describe the assessment of the competence of the nurse lecturers in nursing education. Systematic review of original article using quantitative study. Four data base sources chosen to get original articles: Science Direct, Proquest, Wiley, Scopus. The review method uses the PCO criteria (s). The selected articles have been limited to the criteria of using English, open access and full text, published between 2012 and 2023. Screening and extraction processes employ the Covidence system. Critical appraisal is done using JBI. The proceed of this review its importance knowledge, skills, and attitudes about leadership are proven to be important for increasing the competence of nurse lecturers. Furthermore, lecturers' confidence in their own competence was associated with having entrepreneurial experience and promulgate it to the students. This systematic review provides an overview wheter instruments can be used to assess the competence of nurse lecturers. Competent nurse lecturers will encourage the improvement of the quality of nursing student graduates and nursing education. The main competencies that must be possessed by nurse lecturers include knowledge, skills and attitudes. The competency that is most frequently found is pedagogical competence. By assessing the competence of nurse lecturers through nurse lecturer assessment instruments, it is expected that the quality of nursing education will be maintained.